PERAN PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN IPS DALAM MEMBENTUK NILAI RELIGIUS DAN NASIONALISME DI MTs BAITUL HIKMAH TEMPUREJO TAHUN AJARAN 2024/2025 - Dzikrillah Ibni Mubarok; Agi Ma'ruf Wijaya; Adzkiyak (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study investigates the role of history learning in shaping religious and nationalist values among students at MTs Baitul Hikmah Tempurejo during the 2024/2025 academic year. The background of this research stems from the challenges of globalization and technological development, which have led to the degradation of moral values, weakening of religiosity, and declining sense of nationalism among Indonesian youth. The objective of this study is to describe how history teachers integrate character education into learning processes, identify the religious and nationalist values emphasized, and analyze students’ perceptions of the implementation. The research employs a qualitative approach with a descriptive case study design. Data were collected through interviews, observations, and documentation, while validity was ensured by triangulation and member checks. The findings reveal that religious values are integrated into history lessons by emphasizing the contributions of Islamic leaders, promoting routine religious practices, and reinforcing moral attitudes in daily school activities. Nationalist values are fostered through lessons on the independence struggle, school ceremonies, commemorations of national days, and extracurricular programs such as scouting. Teachers play a crucial role as role models and facilitators, supported by a school environment that cultivates both religious and national character. However, challenges include students’ limited interest in history subjects, inconsistency in practicing values outside school, and limited use of digital media. To address these issues, teachers implement innovative strategies such as digital media use and interactive methods. Overall, the study concludes that history learning serves not only as knowledge transfer but also as an effective medium for strengthening character education, particularly in developing religiosity and nationalism among students.